Can Volcanic Dust Suspended From Surface Soil and Deserts of Iceland Be Transferred to Central Balkan Similarly to African Dust (Sahara)? - Đorđević, Dragana; Tošić, Ivana; Sakan, Sanja; Petrović, Srđan; Đuričić-Milanković, Jelena; Finger, David C.; Dagsson-Waldhauserová, Pavla (Frontiers in Earth Science, 2019)
In this work we use chemical fingerprints as characteristics ratios of specific crustal elements Ca/Al, Fe/Al, K/Al, Mg/Al, Mn/Al, Ca/Fe and Mg/Fe to investigate the long-range transport of volcanic aerosols which are entering the atmosphere in suspended and resuspended processes from Icelandic deserts and hot spots in remote areas in Iceland and transmitted to the central Balkan area (Belgrade). For this purpose, backward trajectories from Belgrade (=44°48’; =20°28’) in 2012 and 2013, simultaneous with atmospheric aerosols measurements, were calculated by using the Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT) model. We found that about 17% of air masses passed over Icelandic territory and arrived to Balkan area. In almost all of these episodes ratios of some investigated elements in suburban aerosols of Balkan area corresponded to the ratios of elements investigated in surface soil of the Rangárvellir area - South Iceland in the vicinity of volcanoes. We identified several episodes, such as 6 – 8 August 2012, 2 – 6 June 2013, 26 – 28 June 2013, and 18 – 20 September 2013, with the characteristic ratios of the highest number of investigated elements in atmospheric aerosol of central Balkan corresponding to ratios from Icelandic soil material. This study provides evidence that Icelandic dust can travel long distances showing the importance of High Latitude Dust sources.